The Impact of Previous Obstetric History on the Risk of Spontaneous Preterm Birth in Women with a Sonographic Short Cervix - Dude, Carolynn M.; Levine, Lisa D.; Schwartz, Nadav (American Journal of Perinatology, 2020)
Objective The natural history of women with a short cervix and a low-risk obstetric history remains poorly defined. In our study, we sought to better characterize the impact of previous obstetric history on the delivery outcomes in women diagnosed with a mid-trimester sonographic short cervix.Study Design We performed a retrospective cohort study of women with singleton gestations who underwent transvaginal cervical length screening between 16 and 24 weeks at two urban hospitals in Philadelphia between January 2013 and March 2018 and were found to have a short cervix (defined as ≤2 cm). Women were excluded from the cohort if there were major fetal anomalies noted or if delivery outcome information was not available. The cohort was then divided into three groups based on obstetric history: nulliparous, history of full-term birth only, or history of spontaneous preterm birth (sPTB). The primary outcome was sPTB <37 weeks, while the secondary outcome was sPTB <34 weeks.Results Our cohort included a total of 384 singleton pregnancies that were diagnosed with a sonographic short cervix: 165 women were nulliparous, 119 women had a history of full-term birth, and 100 women with a history of sPTB. We found that women with a short sonographic cervix had a sPTB rate of 39.6% with no differences found between the three groups. Only two-thirds of nulliparous women and women with a history of full-term birth received the recommended preventative treatment, compared with almost 100% of women with a history of sPTB.Conclusion Women with and without a history of sPTB are at comparable risk of sPTB in the presence of a sonographically short cervix. Preventative therapies should be recommended to both nulliparous women and women with a history of full-term birth since uptake in this population are not as high.
Keywords: short cervix; preterm birth; vaginal progesterone